David Harvey. The urbanization of capital : studies in the history and theory of capitalist urbanization. Baltimore: The Johns Hopkins University Press, 1985. 239 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1986)
DAVID HARVEY. The Urbanization of Capital. Studies in the History and Theory of Capitalist Urbanization. The Johns Hopkins University Press, 1985.